A note on centralizers - Howard E. Bell (International Journal of Mathematics and Mathematical Sciences)
For prime rings R, we characterize the set U∩CR([U,U]), where U is a right ideal of R; and we apply our result to obtain a commutativity-or-finiteness theorem. We include extensions to semiprime rings.